1
$\begingroup$

I'm trying to use that

$$|\cos z| = \left|\frac{1}{2}(e^{iz}+e^{-iz})\right| = \left|\frac{1}{2}(\cos z+i\sin z + \cos -z + i\sin -z)\right| = \left|\frac{1}{2}(2\cos z)\right|$$

but I return to the same thing. Also, I couldn't understand this related question's answers, specially in why

$$\sin^2(x)\cosh^2(y)+\cos^2(x)\sinh^2(y)\\ \ge \sin^2(x) $$

$\endgroup$
  • $\begingroup$ Because $\cosh^2-1 = \sinh^2$ $\endgroup$ – user384138 Nov 3 '16 at 16:02
0
$\begingroup$

Hint. One may write$$ \begin{align} |\cos(z)|^2&=|\cos(x)\cosh(y)+i\sin(x)\sinh(y)|^2\\ &=\cos^2(x)\cosh^2(y)+\sin^2(x)\sinh^2(y)\\ &=\cos^2(x)\cosh^2(y)+(1-\cos^2(x))\sinh^2(y)\\ &=\cos^2(x)(\cosh^2(y)-\sinh^2(y))+\sinh^2(y)\\ &=\cos^2(x)\cdot 1+\sinh^2(y)\\ &\ge \cos^2(x), \end{align} $$ and similarly for $|\sin(z)|^2$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.